DEVELOPMENT OF A SOLAR THERMAL POWER GENERATOR USING WATER LENS-BASED THERMOELECTRIC TECHNOLOGY - Ketut Alit Adi Untara; Nurul Kami Sani; I Wayan Darmadi; Kamaluddin Kamaluddin (Universitas Bhinneka PGRI, 2025)
Solar thermal power generation using thermoelectric technology offers promising potential for renewable energy use in Palu, Indonesia, providing a clean and sustainable source of electricity for low-power electronic devices. This approach not only reduces greenhouse gas emissions but also supports sustainable regional development by offering an alternative to fossil fuels, thus strengthening long-term energy resilience. Additionally, utilizing renewable energy can foster local economic opportunities and decrease energy import costs. This study employs a thermoelectric generator (TEG) that converts heat focused through water lenses into electrical power via the Seebeck effect. The system’s performance depends on the temperature difference created between the heated and cooled sides of the thermoelectric module. Experimental results showed a voltage range of 0.1 V to 0.33 V, producing a current of about 0.001 A, with an output power of 1.0 × 10⁻⁴ W to 3.3 × 10⁻⁴ W. Though the current output supports low-power devices, further optimization is required to enhance efficiency. This research underscores the viability of water lens-based thermoelectric systems as an eco-friendly energy solution in solar-rich regions, presenting a potential pathway for sustainable energy generation.